Dermatologic Lesions in Geriatric Patient with Diabetes Mellitus - Fitriani Fitriani; Damai Trilisnawati; Stella Sunur; Inda Astri Aryani; Nopriyati (HM Publisher, 2020)
Introduction: In geriatrics, there are changes in structure and function results in histopathological, physiological and clinical skin changes. The conditions can cause morbidity and decreases the quality of life of patients. This study was the first study that provide the characteristics of geriatric skin disorders in Dr. Mohammad Hoesin Hospital Palembang. Methods: This study was descriptive observational with cross-sectional design using total sampling method performed among patients in Geriatric Outpatient Clinic, Dermatology and Venereology Outpatient Clinic and geriatric inpatient room in Dr. Mohammad Hoesin Hospital on July-September 2019. Results: Physiological skin changes in geriatrics include xerosis cutis (13,95%), seborrheic keratosis (13,17%), guttate hypomelanosis (8,5%), senile lentigen (6,97%), freckle (2,32%), periorbital hyperpigmentation (1,55%), senile purpura (0,77%) and poikiloderma civatte (0,77%). The most skin disorder found were lichen simplex chronicus (11,1%), pressure ulcers (9,25%), senile pruritus (8,32%), asteatotic dermatitis (6.47%) and candidiasis (3,7%). The most common comorbid condition were diabetes mellitus in 16 patients (22,5%), CVD in 7 patients (9,9%), hypertension in 6 patients (8,5%), AKI in 6 patients (8,5 %), and HHD in 4 patients (5,6%). Diabetes mellitus was significantly associated with xerosis cutis (p = 0,0007), senile pruritus (p = 0,015), and guttate hypomelanosis (p = 0,016). Conclusion: The most physiological skin changes found in geriatric patients in Dr. Mohammad Hoesin Hospital were xerosis cutis, seborrheic keratosis, and guttate hypomelanosis, while skin disorder were lichen simplex chronicus, pressure ulcer, and senile pruritus. Diabetes mellitus was significantly associated with skin disorders.